FORMING THE CONCEPT OF HOSPITALITY IN INNOVATIVE MARKETING SERVICES OF RESTAURANT ENTERPRISES - Matviyiv, Mykola (Journal of European Economy, 2017)
The essence of the hospitality concept in innovative marketing of restaurant companies is considered. The concept of hospitality stems from the relationships marketing concept and has its own field of application related to a friendly reception and quality service guests (customers), restaurants, hotels, cruise ships, casinos, resorts, boarding houses, motels, hostels etc. Two modern directions of hospitality develpoment, namely hospitality providing guests housing and conveniences (hotel industry) and hospitality providing entertainment and catering (restaurant industry) are characterized. The classification of European national cuisines and molecular cuisine, as the fashion trend in cooking that indicate the different dishes with unusual combinations of properties and components is done.